High and low frequency TENS in young people with primary dysmenorrhea: Clinical trial protocol: TENS in dysmenorrhea: protocol - R. M. Amaral, Auxiliadora; C. Araújo , Rodrigo; A. Amorim , Danielly; A. Valença , Amanda; R. Pitangui, Ana Carolina (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: Primary dysmenorrhea (PD) is lower abdominal pain in the absence of an organic cause, common in women under 25 years of age. It is the main cause of school/work absenteeism and presenteeism, therefore, the objective of its treatment is to provide women with adequate pain relief. Pharmacological treatment is characterized as first line, however it is associated with side effects. Transcutaneous Electrical Nerve Stimulation (TENS) is a non-pharmacological and non-invasive complementary therapy for pain management. Objective: To compare the effectiveness of high frequency (HFT) and low frequency (LFT) TENS modalities in relieving pain in young people with PD. Methods: Randomized, controlled and double-blind clinical trial protocol, with young women between 15 and 29 years old, nulliparous, regular menstrual cycle, self-report and presence of PD with pain intensity greater than or equal to three points on the Numerical Assessment Scale (Numeric Rating Scale - NRS). TENS will be randomized into two groups – Group HFT and Group LFT, application of 30 minutes, evaluated over the 24 hours after the intervention, for one menstrual cycle. In analyzing the results, the primary outcome will be the report of pain intensity. Secondary outcomes will be the durability of TAF and TBF analgesia; patient satisfaction and the presence of adverse effects; compare the amount of analgesic intake in the groups; assess the level of physical activity; evaluate the interference of PD symptoms in physical, mental and social activities and verify their interference with school/work presenteeism. Considerations: The present protocol aims to establish an evidence base for optimal recommendations on the use of TENS modalities for the relief of PD in young women.